Peningkatan Hasil Belajar Siswa dalam PAK Melalui Model Problem Based Learning (PBL) Kelas VI Fase C SD Negeri 040533 Merek - Irama Br Sembiring (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to enhance student learning outcomes through the implementation of the Problem Based Learning (PBL) method in the sixth grade of SD Negeri 040533 Merek. The PBL method was chosen for its ability to actively engage students in the learning process by confronting them with real-life problems relevant to their daily lives. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through observations, learning outcome tests, and questionnaires to evaluate student engagement. The results showed a significant improvement in student learning outcomes from Cycle I to Cycle II, with the percentage of mastery learning increasing from 83% to 87%. Additionally, students demonstrated enhanced collaborative skills and critical thinking abilities. These findings indicate that the application of the PBL method not only improves academic learning outcomes but also fosters character development and social skills among students. Therefore, it is recommended that the PBL method be more widely integrated into the curriculum to facilitate more effective and enjoyable learning experiences.